The impact of clean sky technology on future 3500 lb single engine light rotorcraft - Enconniere, Julien; Ortiz-Carretero, Jesus; Goulos, Ioannis; Pachidis, Vassilios; Smith, C.; Stevens, J.; d'Ippolito, R.; Thevenot, Laurent (ISABE, 2017)
This manuscript describes a collaborative research effort between members of the Clean Sky Joint Technology Initiative (JTI), within the broader area of novel rotorcraft engine technology and rotorcraft operations. The Clean Sky JTI was created as a public/private partnership between the European Commission and the aeronautical industry. The paper assesses the impact of innovative engine technologies to be integrated into the next generation of rotorcraft and evaluates their potential towards meeting the ACARE 2020 goals. The focus is on the lower segment of the light helicopter class with a particular interest in the performance of two innovative powerplants: an advanced turboshaft with Lean Premixed Prevaporised (LPP) combustor design and a supercharged diesel cycle engine. In order to evaluate their benefits alongside other Clean Sky technologies, a multi-disciplinary rotorcraft performance analysis framework (PhoeniX) is employed. Two variants of the same light helicopter platform with year 2020 technology plus Clean Sky innovations are modelled, named hereafter as Single Engine Light (SEL) Y2020 and High Compression Engine (HCE) Y2020, respectively. A turboshaft engine-powered helicopter, representative of year 2000 technology (SEL Y2000) is also modelled and used as reference. Payload-Range diagrams (PR) of the three vehicles were generated. The HCE Y2020 reached a maximum range 83% greater than the SEL counterparts. The gaseous emissions of the helicopters were also evaluated over three notional scenarios representative of light helicopter activities. The HCE Y2020 emitted 60% less carbon dioxide (CO2) and 63% less nitrogen oxides (NOx) than the SEL Y2000. The SEL Y2020 emitted on average 19% and 49% less CO2 and NOx, respectively, compared with the SEL Y2000. It was also observed that the NOx production rate of the LPP technology integrated in the SEL Y2020 combustor depends strongly on engine power setting. At certain power settings, the SEL Y2020 emitted less NOx than the HCE Y2020 even though the HCE Y2020 emitted less NOx over the complete mission. The direct comparison between SEL Y2020 and HCE Y2020 highlighted the superior performance of the HCE engine over the gas turbine for the mission types and rotorcraft class simulated.
Keywords: Clean sky; Piston engine; Performance; Emissions; Combustion